Root development of Urochloa humidicola genotypes in hydroponic system - Mayorga, Mildred; Cardoso, Juan Andrés (Bioversity International and the International Center for Tropical Agriculture, 2022)
Urochloa humidicola is a stoloniferous perennial grass adapted to acid infertile soils and waterlogged habitats, additionally it is characterized by its high potential for biological nitrification inhibition (BNI). The implementation of agricultural systems with deep rooting capacity is an alternative to improve SOC storage, since the root is the organ through which carbon fixed through photosynthesis is transported to the soil. It is important to determine the potential for the development of deep roots in plant materials adapted to soils with different conditions because they can additionally improve SOC storage and contribute to the implementation of sustainable agricultural systems.